You Sluice and hai Modification in Chinese - Wei Ting-Chi (Sciendo, 2017)
This paper argues that you ‘have’ sluice is a variant of pseudosluicing, akin to shi ‘be’ sluice in Chinese. You sluice can be analyzed as a base-generated structure [pro you ‘have’ wh-phrase], consisting of a subject pro, a verb you ‘have’, and a wh-phrase, having nothing to do with movement and deletion. In this simple clause, the pro can either refer to a nominal antecedent or an event antecedent; you ‘have’ mainly denotes possessive or existential readings as well as extended attributive uses. This analysis further reveals how circum-phrase chule … yiwei ‘besides’ semantically and syntactically interacts with hai ‘still’ in you sluice to express else modification in English sluicing derived by movement and deletion.